Prognostic factors after transoral resection of early hypopharyngeal cancer. Issue 4 (17th July 2021) - Iritani, Keisuke; del Mundo, Daryl Anne A.; Iwaki, Shinobu; Masuda, Kuriko; Kanzawa, Maki; Furukawa, Tatsuya; Teshima, Masanori; Shinomiya, Hirotaka; Morimoto, Koichi; Otsuki, Naoki; Nibu, Ken‐ichi
Abstract: Objective: This study aimed to investigate risk factors predictive of local recurrence and/or lymph node metastasis after transoral resection of early hypopharyngeal cancer. Methods: Forty‐nine consecutive patients who underwent transoral videolaryngoscopic surgery (TOVS) as an initial treatment for hypopharyngeal cancer were evaluated. On univariate and multivariate analysis, local recurrence rates were assessed respectively using log‐rank test and cox regression analysis according to the following parameters: subsite, pT, mucosal margin, lymphatic invasion, vessel invasion, tumor thickness (> 4 mm vs ≤4 mm), history of esophageal cancer, and multiple Lugol‐voiding lesions (LVLs) in the esophagus. Categorical variables were evaluated for their associations with lymph node metastasis using chi‐squared test or Fisher's exact test. Result: The subsites of primary lesions were piriform sinus in 24 patients, posterior wall in 15 patients, and postcricoid in 10 patients. Thirty patients had esophageal cancer. Local recurrence occurred in 14 patients. Three patients had lymph node metastasis at the time of diagnosis and four patients developed lymph node metastasis after the initial treatment, resulting a total of seven patients having lymph node metastasis. While mucosal margin and LVLs showed significant associations with local recurrence on univariate analysis, only LVLs remained as a significant risk factor on multivariate analysis ( P  = .0395; hazard ratio = 8.897; 95% confidence interval, 1.113‐71.15). Most cases of local recurrence were satisfactorily controlled by repeated TOVS. While multivariate analysis could not be performed due to the small number of the patients with lymph node metastases, venous invasion ( P  = .0166) and tumor thickness ( P  = .0092) were significantly associated with lymph node metastasis on univariate analysis. Conclusions: Local recurrence was more frequent in patients with LVLs, but most of them were salvaged by repeated TOVS. Patients with venous invasion and/or tumor thickness greater than 4 mm should be followed up with special attention to lymph node metastasis. Level of Evidence: 3. Abstract :